Broadcasting Beasts: Review of Claire Molloy, Popular Media and Animals - Vint, Sherryl (Humanimalia, 2013)
Claire Molloy, Popular Media and Animals. London: Palgrave Macmillan, 2011. 256 pp. $85.50 (hb); $72.00 (kindle).